Acetate formation in the photoheterotrophic bacterium Chloroflexus aurantiacus involves an archaeal type ADP‐forming acetyl‐CoA synthetase isoenzyme I. Issue 2 (13th November 2013) - Schmidt, Marcel; Schönheit, Peter
Abstract The bacterium Chloroflexus aurantiacus excreted significant amounts of acetate during photohetero trophic growth on glucose and in resting cell suspensions. Up to 1.5 mol acetate per mol glucose were formed. In acetate‐forming cells, the activities of phosphotransacetylase and acetate kinase, usually involved in acetate formation in Bacteria, could not be detected; instead, the cells contained an acetyl‐CoA synthetase (ADP‐forming) (ACD) (acetyl‐CoA + ADP + Pi → acetate + ATP + CoA), an enzyme so far reported in prokaryotes to be specific for acetate‐forming Archaea. ACD, which was induced 10‐fold during growth on glucose, was purified and the encoding gene was identified as Caur_3920. The recombinant enzyme, a homotetrameric 300‐kDa protein composed of 75‐kDa subunits, was characterized as functional ACD. Substrate specificities and kinetic constants for acetyl‐CoA/acetate and other acyl‐CoA esters/acids were determined, showing similarity of the C. aurantiacus ACD to archaeal ACD I isoenzymes, which are involved in acetate formation from sugars. This is the first report of a functional ACD involved in acetate formation in the domain of Bacteria.